Prevalence and predictors of road crash involvement among medical doctors in Malaysia: a cross-sectional study protocoll - Abdul Rashid, Aneesa; Devaraj, Navin Kumar; Mohd Yusof, Halidah; Mustapha, Fauzan; Wong, Shaw Voon; Ismail, Ahmad Filza; Ismail, Khairil Idham; Qureshi, Ahmad Munir; Nordin, Rusli (BMJ Publishing, 2020)
Introduction Medical doctors are often subjected to long working hours with minimal rest in between the shifts. This has led to many fatal and non-fatal road crash involvement (RCI). This study aims to determine the prevalence and predictors of RCI among medical doctors in Malaysia. Methods and analysis This is a cross-sectional study among 375 Malaysian medical doctors who met the inclusion criteria. A predetermined self-administered questionnaires will be used to collect information regarding the sociodemographic, health status, workplace information, work commuting information, driving behaviour, history of RCI, fatigue, sleep quality, mental health status and work engagement. The questionnaires consist of the following instruments: (1) sociodemographic, health status, workplace information, work commuting information, driving behaviour and history of RCI; (2) Checklist of Individual Strength Questionnaire; (3) Pittsburgh Sleep Quality Index; (4) 21-item Depression Anxiety and Stress Scale; and (5) Utrecht's Work Engagement Scale. The data will be analysed using SPSS program V.24. Descriptive and inferential statistics will be used to determine the prevalence and predictors of RCI. Ethics and dissemination This study protocol has received ethics approval from the Medical Research and Ethics Committee (MREC), Ministry of Health Malaysia (NMRR-18-3983-40609) and the Ethics Committee for Research Involving Human Subject, University Putra Malaysia (JKEUPM). Online written informed consent will be obtained from each study participant by the researchers. Results of the study will be disseminated through relevant journals and conferences.